Hello.
There are 2 basic steps to this particular problem:
1). Plug g(x) into f(x).
2). Simplify.
Step by step:
1).
f(x)= 2 |x+3| -1
g(x)= -4x² -9
So:
f(g(x))= 2 | (g(x)) +3 | -1 ***
f(g(x))= 2 | (-4x² -9)+3 | -1
f (g(x))= 2 | -4x² -9+3 | -1
f (g(x))= 2 | -4x² -6 | -1
*** This is to illustrate how plugging functions into functions works, and is not proper notation.
Hope this helped!
*************************
Disclaimer:
Always double check your answer with a reliable source, as mistakes can be made.